2016
DOI: 10.1111/ffe.12514
|View full text |Cite
|
Sign up to set email alerts
|

2D modelling of inclined intergranular stress corrosion crack paths

Abstract: Inclined high pH stress corrosion cracking (SCC) is a type of intergranular environmental cracking in gas pipelines, which differs from typical SCC by propagating at an angle from the wall direction. Investigations of Australian and Canadian inclined SCC colonies have not provided a clear indicator of a cause for the abnormal crack growth direction. This paper addresses the possibility of crack tip strain enhanced electrochemistry causing the inclination. Potentiodynamic tests were conducted to quantify the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…Through a numerical model under development by the authors, 23 the grain aspect ratio (AR, defined as height of the grain divided by the width) was identified as another possible parameter influencing the crack paths. The model operates under the assumption that the strain in the crack tip plastic zone enhances the current density for dissolution and reduces film stability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through a numerical model under development by the authors, 23 the grain aspect ratio (AR, defined as height of the grain divided by the width) was identified as another possible parameter influencing the crack paths. The model operates under the assumption that the strain in the crack tip plastic zone enhances the current density for dissolution and reduces film stability.…”
Section: Resultsmentioning
confidence: 99%
“…The model operates under the assumption that the strain in the crack tip plastic zone enhances the current density for dissolution and reduces film stability. [23][24][25] The critical plasticity at which the enhanced dissolution offsets, the higher stress intensity factor in the radial direction was determined from metallographic studies. 7 It also incorporates the geometry of the grain boundaries and how they influence the growth direction for the intergranular growth.…”
Section: Crack Paths Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…36 During the studies on the corrosion fatigue behavior of magnesium alloys, it found that the stress loading rate had great influence on the dynamic mechanical corrosion properties of magnesium alloys, such as SCC. To date, investigations on SCC and protection properties of various steels and aluminium alloys have been performed, 79 whereas such investigations are just beginning for magnesium alloys. Therefore, exploring the SCC properties and stress corrosion protection method for magnesium alloys is particularly urgent.…”
Section: Introductionmentioning
confidence: 99%